Investigation of Nanoparticles Dispersion in Sodium Hydroxide (NaOH) Solvent - Wee, S.C. (EDP Sciences, 2016)
Recently, the study on nanoparticles application in enhanced oil recovery (EOR) starts to growth. Nanoparticles have given better indication for EOR development such as in foam stability as its nano size particles can be feasibly dispersed in aqueous solution and easily flow through porous media. Aggregation of nanoparticles are said to be a major contributor for paralyzing nanoparticles dispersion deep into the formation. Hence, in this research sodium hydroxide (NaOH) is used as stabilizing solvents or carrier fluids in enhancing nanoparticles properties to prevent coagulation of nanoparticles when mixed to create a nanofluid. The dispersion of various concentration of silica oxide (SiO2) and aluminium oxide (Al2O3) are examined by using turbidity test. Results from this research show that the silicon dioxide nanoparticles are at best to be mixed in NaOH solvent to retain longer retention time. Â© The Authors, published by EDP Sciences, 2017.